The degree microbiological contamination water of reservoir Sorbulak (Experimental biology, 2015)
In article pollution by microorganisms of a biological reservoir with a method Sorbulak's cultivation which is located in the Iliysky area is defined.It is defined the content of water of a biologicheskiy reservoir of Sorbulak. First with a research objective of microbiological pollution of water, drinking water is necessary unit volume 1 ml waters contains no more quantity of 100 bacteria. Therefore with a research objective extent of microbiological pollution experiment is made. If the coefficient of divorce 106, number of microorganisms about 3 million to mean actively grows.
Keywords: autochthonous and allochthonous microorganisms polysaprobic zone; wastewater; bacteria; treatment biological